2008
DOI: 10.1097/mca.0b013e32830042ba
|View full text |Cite
|
Sign up to set email alerts
|

The association of serum prolidase activity with the presence and severity of coronary artery disease

Abstract: Findings of this study have shown that serum prolidase activity is significantly associated with the presence and severity of CAD, and elevated serum prolidase activity might be an independent predictor of coronary atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 38 publications
3
53
1
Order By: Relevance
“…Moreover, the degree of severity of oxidative stress is directly correlated with the inhibition of collagen production, and prolidase is supposed to be the target enzyme of this process (Sienkiewicz et al, 2004). Yildiz et al (2008) showed that serum prolidase activity in an increasing manner was significantly associated with the presence and severity of CAD. In addition, it was suggested that hypertension and its duration are associated with increased serum prolidase activity, and it may be a marker for the follow-up of hypertensive patients (Demirbag et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the degree of severity of oxidative stress is directly correlated with the inhibition of collagen production, and prolidase is supposed to be the target enzyme of this process (Sienkiewicz et al, 2004). Yildiz et al (2008) showed that serum prolidase activity in an increasing manner was significantly associated with the presence and severity of CAD. In addition, it was suggested that hypertension and its duration are associated with increased serum prolidase activity, and it may be a marker for the follow-up of hypertensive patients (Demirbag et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Its activity has been documented in plasma, erythrocytes, leukocytes, dermal fibroblasts, and various organs, such as kidney, brain, heart, thymus, uterus, liver, small intestine, stomach, spleen, lung, and pancreas (Zanaboni et al, 1994;Liu et al, 2007). Prolidase activity has been investigated in various disorders, such as chronic liver disease (Myara et al, 1984), osteoporosis (Erbagci et al, 2002), osteoarthritis (Altindag et al, 2007), uremia (Gejyo et al, 1983), and hypertension (Demirbag et al, 2007), and in the presence and severity of coronary artery disease (Yildiz et al, 2008).…”
mentioning
confidence: 99%
“…15 Briefly, 1 ml of buffer containing 0.1 M Tris; 10 mmol/l EDTA ( pH 8.2); and 50 ml of serum, was added to cuvettes, followed by 50 ml of 10 mmol// 5,5 ′ -dithiobis(2-nitrobenzoic acid) in methanol. Blanks were run for each sample as a test.…”
Section: Measurement Of Total Free Sulfhydryl Groupsmentioning
confidence: 99%
“…Previously it has been shown that prolidase activity in normal fibroblasts is regulated by the interaction of extracellular matrix proteins, mainly type I collagen with b1 integrin receptor (Palka and Phang 1997). Previous clinical studies have shown increased serum prolidase activity, which indicates increased collagen turnover, in chronic liver disease, coronary artery disease (Myara et al 1984;Yildiz et al 2008). Conversely deficient/reduced serum prolidase activity was reported to be associated with lupus-like syndrome characterized by nonhealing skin ulcers owing to defective collagen turnover (Shrinath et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme plays a key role in the recycling of proline for collagen turnover and cell growth. Prolidase enzyme activity has been investigated in various disorders such as chronic liver disease, coronary artery disease (Myara et al 1984;Yildiz et al 2008).…”
mentioning
confidence: 99%